Program Design and the Development of Students' Global Perspectives in Faculty-Led Short-Term Study Abroad. (July 2021) - Whatley, Melissa; Landon, Adam C.; Tarrant, Michael A.; Rubin, Donald
This study explores connections between design features of faculty-led short-term study abroad programs and resulting changes in students' global perspectives. Over 2, 000 students provided data for this study, completing the Global Perspective Inventory (GPI) before and after studying abroad. Results indicated that program features such as participation in an internship and opportunities for reflection are positively associated with global perspective development while abroad, whereas features such as number of students traveling together and coursework in English are negatively associated with such development. Given the increasing numbers of students who participate in faculty-led short-term abroad programs, research that provides evidence-based recommendations concerning program design is essential to enhancing global perspectives through study abroad.